Framing sustainable performance with the Six-P - Carleton, Karen (My University, 2009)
A systemic needs assessment can help close performance gaps for continuous improvement. The Six-P framework assesses organizational sustainability with six elements: perception, potential, practice, profit, planet, and people. It builds on Kirkpatrick’s evaluation model, Phillips’s return on investment, and a triple bottom-line focus, facilitating corporate social responsibility. The framework, with its question guide and suggested assessment methods, highlights the importance of societal and environmental performance. The case study in this article illustrates the application of the Six-P framework for assessing sustainability.
Keywords: needs assessment; sustainability